The Effect of Temporary Changes and Expectations on Individuals' Decisions: Evidence from a Tax Compliance Setting - Austin, Chelsea Rae; Bobek, Donna D.; LaMothe, Ethan G. (The Accounting Review, 2020)
ABSTRACT Based on prospect theory's value function, we predict how reference points adapt to influence individuals' tax evasion choices during and after experiencing temporary tax changes. Results from a multi-round experiment indicate reactions to temporary changes depend jointly on the direction of the change and expectations. Specifically, individuals experiencing a tax increase evade more while the increase is in effect. More interestingly, knowing, versus not knowing, a tax decrease is temporary prevents an increase in evasion after the temporary change expires, and may lead individuals to reduce evasion during the change. In a supplemental condition, we induce uncertainty by repeatedly extending a tax decrease. We find when uncertainty is introduced, both benefits of knowing the temporal nature of the decrease are lost. Overall results are consistent with individuals failing to adapt to a loss state and adapting quickly to a gain state unless they are certain the gain state is temporary.